Scientific Data Visualization with Shape Preserving C1 Rational Cubic Interpolation (European Journal of Pure and Applied Mathematics, 2010)
This paper deals with the shape preserving C1 rational cubic interpolation. The developed rational cubic interpolating function has only one free parameter. The approximation order of rational cubic function is investigated and range of optimal error constant is determined. Moreover, positive, constrained and monotone data preserving schemes are developed.
Keywords: Rational cubic; Spline; Peano Kernel theorem; Interpolation; Visualization